2004
DOI: 10.1021/la049667f
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer Assembly of Prussian Blue Nanoclusters and Enzyme-Immobilized Poly(toluidine blue) Films and Its Application in Glucose Biosensor Construction

Abstract: A multilayered glucose biosensor via sequential deposition of Prussian blue (PB) nanoclusters and enzyme-immobilized poly(toluidine blue) films was constructed on a bare Au electrode using electrochemical methods. The whole configuration of the present biosensor can be considered as an integration of several independent hydrogen peroxide sensing elements. In each sensing element, the poly(toluidine blue) film functioned as both the supporting matrix for the glucose oxidase immobilization and the inhibitor for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(61 citation statements)
references
References 36 publications
5
55
1
Order By: Relevance
“…[4][5][6] Therefore, different chemically modified electrodes have been developed for biomolecular analysis, environmental monitoring, and analysis of food quality. [7][8][9][10][11] Functional modification of electrode substrates for the construction of electrochemical biosensors having improved analytical performance with respect to other biosensor designs is highly desirable for developing potential device applications.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Therefore, different chemically modified electrodes have been developed for biomolecular analysis, environmental monitoring, and analysis of food quality. [7][8][9][10][11] Functional modification of electrode substrates for the construction of electrochemical biosensors having improved analytical performance with respect to other biosensor designs is highly desirable for developing potential device applications.…”
Section: Introductionmentioning
confidence: 99%
“…At the reduction potential of H 2 O 2 , oxidation of interference species such as AA does not occur. [17][18][19] Here, we report an alternative approach for depleting interfering electroactive species based on the theory of the electrochemical diffusion layer. When the electrochemical Abstract: A dual-electrode configuration for the highly selective detection of glucose in the diffusion layer of the substrate electrode is presented.…”
Section: Introductionmentioning
confidence: 99%
“…12,29 In subsidiary experiments we observed that bare ITO and ITO modified with PB used in amperometric measurements failed to detect lactose.…”
Section: ■ Results and Discussionmentioning
confidence: 92%